If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2v + 2 = -10 Reorder the terms: 2 + 2v = -10 Solving 2 + 2v = -10 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2v = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 2v = -10 + -2 2v = -10 + -2 Combine like terms: -10 + -2 = -12 2v = -12 Divide each side by '2'. v = -6 Simplifying v = -6
| 4x^2-20X+9=0 | | 2x+14=-96-9x | | 5m+2=31 | | 4a+3=41 | | 3x(4x+3x)=24 | | 3x(4-2x)=21 | | -2x+5y=0 | | 147-3x=6x+21 | | 3x(4x+3x)=21 | | 5x-5+3x+3=180 | | 4x-17-6x+24=19-8x | | 3(4-2)=24 | | 4x-17-6x+24=19-9x | | 3X^2-7=5 | | 79=4f-1 | | 5y=z | | 6x+17=-24+6x | | 6d-2=40 | | -22=-6w+2(w+5) | | 50-3x=6x+17 | | 0=-x-3 | | p(3p+2)=0 | | 13-7x=109-28x | | (4x-6)+(5x+7)= | | =(4x-6)+(5x+7) | | 17+2n=87 | | (b+4)(2b-5)=0 | | X-2(-1)=6 | | 4(2y+3)-5(y+3)= | | x*2x+x*10= | | 58-2x=10x+22 | | 118-6x=10x-22 |